2016
DOI: 10.1111/jiec.12498
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Measuring Techniques for Occupational Exposure during Additive Manufacturing of Metals: A Pilot Study

Abstract: SummaryAdditive manufacturing that creates three-dimensional objects by adding layer upon layer of material is a new technique that has proven to be an excellent tool for the manufacturing of complex structures for a variety of industrial sectors. Today, knowledge regarding particle emissions and potential exposure-related health hazards for the operators is limited. The current study has focused on particle numbers, masses, sizes, and identities present in the air during additive manufacturing of metals. Meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 13 publications
(31 reference statements)
7
84
0
Order By: Relevance
“…For example, recently, Kim and colleagues () found that FFF 3D printers, regardless of the material used, emitted nano‐size particles at high concentrations, several aldehydes (including carcinogenic formaldehyde), phthalates, and VoCs such as toluene and ethylbenzene. In another example, Graff and colleagues () recently determined that there was significant operator exposure to metal particles larger than 300 nanometers (>10 8 particles per cubic meter over 10‐second cycles) when handling metal powders for SLS printing. Whereas welding processes, laser printers, and toasters have been known to produce similar concentrations of particulates, the toxicological profile of nanoparticles produced from AM plastics by FFF as well as certain metals like cobalt for SLS could be more harmful (Oberdörster et al.…”
Section: Methodsmentioning
confidence: 99%
“…For example, recently, Kim and colleagues () found that FFF 3D printers, regardless of the material used, emitted nano‐size particles at high concentrations, several aldehydes (including carcinogenic formaldehyde), phthalates, and VoCs such as toluene and ethylbenzene. In another example, Graff and colleagues () recently determined that there was significant operator exposure to metal particles larger than 300 nanometers (>10 8 particles per cubic meter over 10‐second cycles) when handling metal powders for SLS printing. Whereas welding processes, laser printers, and toasters have been known to produce similar concentrations of particulates, the toxicological profile of nanoparticles produced from AM plastics by FFF as well as certain metals like cobalt for SLS could be more harmful (Oberdörster et al.…”
Section: Methodsmentioning
confidence: 99%
“…Three articles in this Special Issue address these topics (Graff et al. ; Mendes et al. ; Azimi et al.…”
Section: Health and Safety Considerationsmentioning
confidence: 99%
“…Three articles contained in this Special Issue focus on the hazards inherent to machine emissions and operator exposure. The paper by Graff and colleagues () experimentally investigates particle numbers, masses, sizes, and identities present in the air during the operation of metallic AM processes, indicating that nano‐sized particles are present in the process environment and that operators are exposed specifically while handling the metal powder. Mendes and colleagues () characterize emissions from a low‐end 3D printer based on the extrusion of polymers, showing that the process emits nanoparticles inside the chamber, and negligible emissions in room experiments, with emission rates depending strongly on extruder temperature.…”
Section: The Special Issue: Charting Impacts Across the Product Life mentioning
confidence: 99%
See 1 more Smart Citation
“…; Graff et al. ; Mendes et al. ) and unit energy consumption will contribute building blocks to future LCA and other systems‐oriented work that is typical of IE.…”
mentioning
confidence: 99%